2002
DOI: 10.1515/bc.2002.068
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extract Protects against Early Alcohol-Induced Liver Injury in Rats

Abstract: Oxidants have been shown to be involved in alcohol-induced liver injury. This study was designed to test the hypothesis that the antioxidant polyphenolic extract of green tea, comprised predominantly of epigallocatechin gallate, protects against early alcohol-induced liver injury in rats. Male Wistar rats were fed high-fat liquid diets with or without ethanol (10-14 g kg(-1) day(-1)) and green tea (300 mg kg(-1) day(-1)) continuously for 4 weeks using an intragastric enteral feeding protocol. Mean body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 29 publications
4
46
0
1
Order By: Relevance
“…In the present study, EGCG concurrent treatment significantly prevented alcohol-induced liver injury as evidenced by a marked blunting of elevation in serum ALT levels and absence of necrosis in liver histology, which is consistent with Arteel GE et al's study with green tea extract [9]. In our study, rats in dextrose group developed slight steatosis in the liver, but almost normal liver histology was seen in dextrose/EGCG group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, EGCG concurrent treatment significantly prevented alcohol-induced liver injury as evidenced by a marked blunting of elevation in serum ALT levels and absence of necrosis in liver histology, which is consistent with Arteel GE et al's study with green tea extract [9]. In our study, rats in dextrose group developed slight steatosis in the liver, but almost normal liver histology was seen in dextrose/EGCG group.…”
Section: Discussionsupporting
confidence: 92%
“…Epigallocatechin-3-gallate (EGCG) is the major constituent of the catechins, and has been shown to possess numerous biological functions, including antioxidant, anti-inflammatory, anticancer effects [5][6][7]. It was reported that green tea or its extract protects against alcohol-induced liver injury in rats [8,9]; however, the mechanisms are not fully defined. In this study, we employed ethanol plus fish oil gavage female rat model of alcohol-induced liver disease, and investigated the effects of EGCG on intestinal permeability and endotoxemia, and inflammatory factors, such as TNF-α, cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) expressions in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with the findings reported by Soliman et al 28 However, coadministration of GTE with GM in Group 4 revealed renoprotective effects and showed only mild infiltration (Figure 3). The renoprotective effect of GTE has been previously reported by Arteel et al 12 and Khan et al 9 It has been suggested that oxidative stress may contribute to the progression of renal damage, 36 hence antioxidants may provide protection against disease onset or progression. GTE polyphenols possess antioxidant properties and appear to be potent scavengers of hydroxyl radicals (OH − ), known for their damaging effects on cellular macromolecules.…”
Section: Discussionmentioning
confidence: 79%
“…The animals of Group 1 served as control. Group 2 received an oral administration of 300 mg/kg/day GTE tablets (750 mg GTE/ tablet; EL Obour Pharma for techno made group, El Obour city Egypt) continuously for 30 days using an intragastric enteral feeding protocol 12 and served as the GTE group. Group 3 was injected subcutaneously with GM (Sigma chemical, St. Louis, MO, USA) 50 mg/kg twice daily for 15 consecutive days 13 and served as the GM group.…”
Section: Experimental Designmentioning
confidence: 99%
“…Antioxidant treatment in vitro has been demonstrated to protect hepatocytes overexpressing CYP2E1 from the synergistic toxicity of polyunsaturated fats such as arachidonic acid and iron [11]. Similarly, in vivo, feeding with the glutathione precursor L-oxothioazolidine-4-carboxylic acid and with dietary antioxidant extracts from cocoa and green tea, as well as gene therapy resulting in hepatic overexpression of either Cu/Zn or Mn superoxide dismutase has been shown to be protective against ALD [4,[12][13][14][15][16]. It is noteworthy that these later observations were performed in rat intragastric ethanol-infusion models such as that originally developed by Tsukamoto et al [5] where pathology is accompanied by endotoxemia and Kupffer cell activation as measured by increased production of oxidants via NADPH oxidase and increased expression of the endotoxin receptor CD14 [4,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%